Sistem Komunikasi Pemerintah Dalam Pelestarian Budaya Karapan Sapi : Studi Kasus Di Kabupaten Sampang - Shella Anggita Pramestika; Dwiningtyas Padmaningrum; Emi Widiyanti (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Cultural preservation is one of the tasks of the Sampang Regency Government to maintain the cow race culture as one of the local cultural potentials of the region. The Sampang Government's communication system is very limited even though the system must remain balanced, so that the system can maintain its existence against environmental changes that occur. Some problems to date have not been able to be solved due to budget constraints, limited knowledge and communication intensity between the government and preservationists. The purpose of this research is to analyse the government's communication system in preserving the culture of the bull race. This research method uses a qualitative approach with a case study to analyse and examine the phenomenon of problems in the culture of cattle racing in Sampang Regency. The results of the study The communication system carried out by the Regional Government of Sampang Regency in the preservation of bull race culture includes several elements such as communication elements, message quality and the relationship between communicators and communicants: (1) communication elements include communicators, namely related agencies (Disperta KP and Disporabudpar), message content and communication media used by each communicator element. (2) problems and message quality there are two types of problems, namely events and livestock care in the quality of messages conveyed by the government has not been in accordance with what is needed so that problems are difficult to solve (3) communicator and communicant elements.